2015
DOI: 10.5812/aapm.31524
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Gabapentin to Prevent Postoperative Shoulder Pain After Laparoscopic Ovarian Cystectomy: A Randomized Clinical Trial

Abstract: Background:Patients undergoing gynecology laparoscopy frequently experience shoulder pain as a common postoperative complication. Considering diaphragm stimulation in its pathophysiology, there are some advice to prevent or control this special form of referral pain.Objectives:The current study aimed to assess the prophylactic effect of preoperative administration of oral gabapentin to prevent Post Laparoscopic Shoulder Pain (PLSP) after laparoscopic ovarian cystectomy.Patients and Methods:In a randomized, dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The lack of a clear benefit with gabapentin use correlates with a recently reported double-blind randomized trial demonstrating that gabapentin did not reduce postoperative pain with first trimester surgical abortion [22]. When considering these findings together with the benefit of pre-emptive gabapentin for pain reduction with abdominal hysterectomy [8][9][10][11][12][13][14], and the slight and variable pain reduction benefit with cesarean delivery [15][16][17][18][19][20], perhaps gabapentin is more beneficial for incision-related (sensory) pain and less for uterine cramping related (visceral) pain.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The lack of a clear benefit with gabapentin use correlates with a recently reported double-blind randomized trial demonstrating that gabapentin did not reduce postoperative pain with first trimester surgical abortion [22]. When considering these findings together with the benefit of pre-emptive gabapentin for pain reduction with abdominal hysterectomy [8][9][10][11][12][13][14], and the slight and variable pain reduction benefit with cesarean delivery [15][16][17][18][19][20], perhaps gabapentin is more beneficial for incision-related (sensory) pain and less for uterine cramping related (visceral) pain.…”
Section: Discussionmentioning
confidence: 84%
“…A systematic review demonstrated a significant benefit of pre-operative gabapentin for preemptive analgesia for abdominal hysterectomy [14]. Data regarding preoperative gabapentin use in other contexts, such as Cesarean delivery and laparoscopic ovarian cystectomy, are less consistent [15][16][17][18][19][20]. The heterogeneity of gabapentin dosing and overall pain regimen along with study design limitations make these data challenging to generalize to abortion procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Valadan et al . revealed preoperative administration of gabapentin reduced the occurrence and severity of SP after laparoscopic ovarian cystectomy . Thus the other drugs than opioids were indicated to be useful for relief from SP, which might help to decrease the opioids use.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis among women undergoing total abdominal hysterectomy has demonstrated decreased opioid consumption and decreased pain scores for the first 24 hours after surgery with preoperative gabapentin (30). Preoperative gabapentin or pregabalin has also been shown to significantly decrease post-laparoscopy shoulder pain in women undergoing laparoscopic gynecologic surgery (31,32). The use of gabapentinoids should be considered in patients undergoing major reproductive/gynecological surgeries, particularly patients at high risk for difficult to control postoperative pain.…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%